Giant Intraperitoneal Multiloculated Pseudocyst in a Male - Jacqueline Oxenberg (Case Reports in Surgery)
Intraperitoneal pseudocysts are rare and may be difficult to differentiate from other malignant neoplasms. Reports of occurrences are mainly associated with long-term intraperitoneal catheter use, intraperitoneal catheter infections, or major pelvic surgery in females, although there are few reported incidences without prior trauma. We present a case of a male patient found to have a 19 × 15 × 9 cm intraperitoneal pseudocyst with other multiloculated areas and a history of a right inguinal hernia repair. After a thorough review of the literature, this is the first multiloculated nonpancreatic pseudocyst reported in a male patient.